The Benefit of Waste Bank for Poor Families in Sicanang Belawan, Medan, North Sumatra - Ananda Mahardika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Waste bank-based management concept is needed to be able to recycle the waste produced by each individual in the household. The presence of SJM (Simpan Jadi Mas)Waste Bank on sub village V of Sicanang, Belawan, Medan City, is managed to change the paradigm of people who formerly saw the waste as a dirty, disgusted object and had no meaning, but now it has turned into something which is valuable and can be saved. Based on that, this study will see how the use of waste savings for poor families in Belawan Sicanang village of Medan. In this study, it will be described some theoretical descriptions related to the concept, the advantages of waste banks and waste savings as well as the poor families. The research method used a qualitative approach with five poor families as the subjects who become the customers of SJM Waste Bank. The data collection technique used is in-depth interviews with data analysis technique used a qualitative approach of interactive model as proposed by Miles and Huberman. The results of this study found that there are two advantages resulting from the waste savings they are economic advantages and social advantages. The economic advantages are marked by extra income of poor families used to meet the food needs, to meet the cost of children’s meals and to help the rental cost of boat. Meanwhile the advantages of waste savings socially is there are a change in behavior that is marked by a change of behavior in sorting the inorganic waste by types and the increasing participation in preserving the environment. Besides that, there is individual skills improvement on poor families which is marked by the ability to recycle the inorganic waste into creation things.